An investigation on temperature-dependant surface properties of porous carbon nanoparticles derived from biomass - S., Supriya; Bhat, Vinay S.; Jayeoye, Titilope John; Rujiralai, Thitima; Chong, Kwok Feng; Hegde, Gurumurthy (Springer Berlin Heidelberg, 2021)
In this work, a detailed investigation on the temperature-dependant surface features of biomass derived porous carbon nanoparticles was conducted. The carbon nanoparticles were prepared by carbonization of Caesalpinia Sappan waste pods in single step pyrolysis, using a range of temperature from 400 to 1000 °C. The systematic analysis of materials obtained at different temperatures assisted to correlate the effect of pyrolysis temperature on the surface properties. Different methods were employed which were beneficial to demonstrate the overall surface area and porous features constituted by pores of different size (micropores, mesopores) and shapes such as cylindrical or narrow slit shape. This study confirmed the optimization of material properties with rise in pyrolysis temperature; as a result, Caesalpinia Sappan derived carbon nanoparticles pyrolyzed at 1000 °C (CSCNP1000) exhibited the largest surface area (794 m2 g−1 by BET) and pore volume (0.37 cm3 g−1) in the series. The resulted carbon products were microporous/mesoporous in nature, the condition which is considered suitable for the energy storage applications. The energy storage device, supercapacitor, was fabricated which exhibited a specific capacitance of 170.5 F g−1 at 0.25 A g−1. This work demonstrated the suitability of temperature dependent surface of a carbon nanoparticle to be actively used as a cost-effective energy storage device.